2020
DOI: 10.5964/ejop.v16i1.1730
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of depression and malingering: An exploratory investigation

Abstract: Malingering mental disorder for financial compensation can offer substantial rewards to those willing to do so. A recent review of UK medico-legal experts’ practices for detecting claimants evidenced that they are not well equipped to detect those that do. This is not surprising, considering that very little is known regarding why individuals opt to malinger. A potential construct which may influence an individual’s choice to malinger is their knowledge of the disorder, and when one considers the high levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Participants were given a vignette depicting a patient with depression and were instructed to rate their social distance in relation to the person in the vignette. The vignette using patient with depression was chosen in this study because depression has been closely associated with malingering, such as being absence from work using depression as an excuse [ 29 ], which may influence the stigmatized view of public towards patients with depression in a workplace environment. The ASD scale was developed [ 30 ] and has been validated [ 27 ] (Cronbach’s α of 0.89 in the present sample), and we used the Japanese version of the scale [ 7 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants were given a vignette depicting a patient with depression and were instructed to rate their social distance in relation to the person in the vignette. The vignette using patient with depression was chosen in this study because depression has been closely associated with malingering, such as being absence from work using depression as an excuse [ 29 ], which may influence the stigmatized view of public towards patients with depression in a workplace environment. The ASD scale was developed [ 30 ] and has been validated [ 27 ] (Cronbach’s α of 0.89 in the present sample), and we used the Japanese version of the scale [ 7 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Albeit in the study of Kanser et al (2019), simulators exhibited longer response times than TBI patients, Fuermaier et al (2020) unexpectedly found that simulators took significantly less time than patients to complete the test. This might result from using different malingering strategies (Cartwright & Donkin, 2020). A recent study about the malingering of depression found that previous knowledge of depression-related symptomatology led to differences in the malingering strategy (Cartwright & Donkin, 2020), which was not controlled in the studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…This might result from using different malingering strategies (Cartwright & Donkin, 2020). A recent study about the malingering of depression found that previous knowledge of depression-related symptomatology led to differences in the malingering strategy (Cartwright & Donkin, 2020), which was not controlled in the studies mentioned above. Additionally, previous studies had found that longer response times associated with simulation are often the result of (a) using a slowed responding strategy; (b) an overestimating of the slowed cognitive processing in persons with TBI; or (c) the additional cognitive processing required in the deception versus truthfulness decision (Kireev et al, 2013; Sun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of mild depression were chosen to be simulated as the mental illness 1PP anti-stigma intervention scenario for three main reasons. First, the symptoms of depression by itself may increase the stigma of the general public towards patients with depression 34 , such as being absent from work using depression as an excuse (i.e. malingering) 34 .…”
Section: Introductionmentioning
confidence: 99%